Creating targeted online career service interventions : survey of students’ career guidance needs in portuguese higher education - Khurumova, Veronika (2022)
Under modern economic conditions, universities have found themselves involved in a competition with each other in the developing market of educational services. Almost any higher educational institution nowadays faces a question of its alumni employability and the career services, among other initiatives, have been established in many universities to improve the competitiveness of their graduates in the labor market. Although the majority of universities in Portugal indicate the existence of a Career Office or a similar entity in the institution, the provision of career counselling services is not fully developed in many. In order to aid the development of career services, recipients’ (i.e. students’) specific requirements need to be assessed to support the understanding and meeting of expectations. What are the Portuguese students’ current career needs and intervention preferences? Which online career guidance intervention would be welcomed, if any? The present study addressed these questions by analyzing data from an online survey administered to 361 Portuguese higher education students. The findings indicate the preferred modalities for career interventions, the current career support needs and the likelihood of joining an online or computer-assisted career counseling service if it were made available by their university. The study’s findings can contribute to the promotion of students’ employability by providing recommendations on the development of Career Offices at Portuguese universities through the creation of targeted career guidance programs, including online interventions.